Minor psychiatric disorders among Brazilian ragpickers: a cross-sectional study - Fassa Anaclaudia; da Silva Marcelo; Kriebel David (BMC, 2006)
Abstract Background Ragpickers are informal workers who collect recyclable materials to earn a small wage. Their life and working conditions are extremely difficult. We examined minor psychiatric disorders (MPD) among a cohort of ragpickers in Pelotas, a city in southern Brazil. Methods Ragpickers were matched by sex, age, and years of schooling with a sample of non-ragpickers from the same poor neighborhoods. The cross-sectional study gathered data by interview on 990 individuals in 2004. MPD were assessed using a standard self-reporting questionnaire, the SRQ-20. Results The prevalence of MPD among ragpickers was 44.7%, higher than reported by neighborhood controls (33.6%; p < 0.001). MPD were more common among females, those of lower economic level, smokers and alcoholics. Among occupational characteristics, MPD prevalence was associated with frequent static postures, low job satisfaction and recent work accidents. Conclusion Ragpickers more frequently report MPD than other poor workers living in the same neighborhoods, with many of the same life conditions. Improving the work lives of these precarious workers should address not only the physical hazards of their jobs but their mental and emotional health as well.